Biomechanical optimization study of posterior tilt extension stems in the repair of tibial plateau bone defects - Wang, Yong; Hao, Ruihu; Guo, Lin; Zhou, Xiaoyu (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundTibial plateau bone defect represents a pivotal challenge in revision knee arthroplasty, where suboptimal extension stem design predisposes to stress concentration and subsequent prosthesis loosening. Physiological posterior tibial slope (5°–7°) optimizes knee biomechanics, yet bone defects disrupt proximal tibial anatomy, rendering traditional stems biomechanically incompatible. The synergistic optimization of “defect severity-stem length-posterior tilt angle” remains underexplored.MethodsA finite element model was constructed incorporating three defect areas (20%, 40%, 60%), two stem lengths (40mm, 80 mm), and five posterior tilt angles (0°–10°), yielding 30 experimental cohorts. Under 2450N axial loading, stress distribution (cortical/cancellous bone, prosthesis, sleeve) and bone-prosthesis micromotion were quantitatively evaluated.ResultsAll micromotion magnitudes remained below the 150 μm osseointegration threshold. In 20% defects, 40 mm stems with ≤7° tilt mitigated cortical stress concentration; 80 mm stems showed lower micromotion but excessive cancellous stress at 10° tilt. In 40%/60% defects, increasing tilt reduced micromotion (37.3%/45.3% reduction), with 80 mm stems exhibiting superior stability. Extreme tilt (10°) in long stems exacerbated cortical stress and prosthesis load.ConclusionBased on the finite element analysis results, this study provides a hypothetical reference for the selection of posterior tilt angles of extension stems in the repair of tibial plateau defects: a posterior tilt angle of ≤7° is suggested for 20% defects when using a 40 mm stem; 7°–10° for 40% defects when using an 80 mm stem; and 5°–7° for 60% defects when using an 80 mm stem. This preliminary biomechanical finding offers a basis for exploring personalized implant design, while the realization of precision-based repair and improved prosthesis longevity requires further validation by multi-center clinical data, diverse patient anatomical models (e.g., differences in tibial size and medullary canal morphology), and in vitro experiments.These data need to be verified through multi-center clinical data and in vitro artificial bone experiments.